Light distribution in fat cell layers at physiological temperatures - Yanina, Irina Yu; Dyachenko, Polina A.; Abdurashitov, Arkady S.; Shalin, Alexander S.; Minin, Igor V.; Minin, Oleg V.; Bulygin, Andrey D.; Vrazhnov, Denis A.; Kistenev, Yury V.; Tuchin, Valery V. (Scientific Reports [Еlectronic resource])
Adipose tissue (AT) optical properties for physiological temperatures and in vivo conditions are still insufficiently studied. The AT is composed mainly of packed cells close to spherical shape. It is a possible reason that AT demonstrates a very complicated spatial structure of reflected or transmitted light. It was shown with a cellular tissue phantom, is split into a fan of narrow tracks, originating from the insertion point and representing filament-like light distribution. The development of suitable approaches for describing light propagation in a AT is urgently needed. A mathematical model of the propagation of light through the layers of fat cells is proposed. It has been shown that the sharp local focusing of optical radiation (light localized near the shadow surface of the cells) and its cleavage by coupling whispering gallery modes depends on the optical thickness of the cell layer. The optical coherence tomography numerical simulation and experimental studies results demonstrate the importance of sharp local focusing in AT for understanding its optical properties for physiological conditions and at AT heating.